New insights into the gut as the driver of critical illness and organ failure. Issue 2 (April 2017) - Meng, Mei; Klingensmith, Nathan J.; Coopersmith, Craig M.
Abstract : Purpose of review: The gut has long been hypothesized to be the 'motor' of multiple organ dysfunction syndrome. This review serves as an update on new data elucidating the role of the gut as the propagator of organ failure in critical illness. Recent findings: Under basal conditions, the gut absorbs nutrients and serves as a barrier that prevents approximately 40 trillion intraluminal microbes and their products from causing host injury. However, in critical illness, gut integrity is disrupted with hyperpermeability and increased epithelial apoptosis, allowing contamination of extraluminal sites that are ordinarily sterile. These alterations in gut integrity are further exacerbated in the setting of preexisting comorbidities. The normally commensal microflora is also altered in critical illness, with increases in microbial virulence and decreases in diversity, which leads to further pathologic responses within the host. Summary: All components of the gut are adversely impacted by critical illness. Gut injury can not only propagate local damage, but can also cause distant injury and organ failure. Understanding how the multifaceted components of the gut interact and how these are perturbed in critical illness may play an important role in turning off the 'motor' of multiple organ dysfunction syndrome in the future.